Strategi Manajerial Pesantren dalam Meningkatkan Kemandirian Santri di Era Digital - Candra Mochamad Surya; Asep Supriatna; Hasan Al Banna; Saepudin Saepudin; Haris Sandi Yudha (Journal on Education, 2025)
The independence of Islamic boarding schools in the digital era faces major challenges related to time management, entrepreneurship and the use of technology. This research aims to identify and analyze the managerial strategies implemented by the Miftahul Khoirot Islamic Boarding School in increasing the independence of students in the digital era. The method used in this research is a qualitative descriptive approach with data collection techniques through interviews, observation and documentation. Data sources for this research include Islamic boarding school administrators, caregivers, and students. The collected data was then analyzed using qualitative data analysis techniques through data reduction, data presentation and drawing conclusions. The research results show that the Miftahul Khoirot Islamic Boarding School has implemented an entrepreneurship program involving students, but the students still need further assistance in managing their businesses. In addition, challenges related to time management, independent decision making, and access to digital learning are also obstacles. Device limitations and internet network quality influence the effectiveness of digital learning implemented. The implication of this research is the need to strengthen technological infrastructure, more intensive entrepreneurship training, and better time management for students, so that they can be more independent in facing challenges in the digital era.